Cress [compact disc, unabridged] - Meyer, Marissa (Meyer, Marissa. Lunar chronicles, 2014)
Cinder and Captain Thorne are fugitives on the run, with Scarlet and Wolf in tow. Together, they're plotting to overthrow Queen Levana and prevent her army from invading Earth. When a daring rescue goes awry, the group is splintered. Cress finally has her freedom, but it comes at a higher price than she'd ever expected. Meanwhile, Queen Levana will let nothing prevent her marriage to Emperor Kai, especially the cyborg mechanic.